Analysis of Academic Efficiency of subsequent courses, in distance and in-person modalities, offered by the Federal Institute of Amapá (2018) (Research, Society and Development, 2020)
The Federal Institutes, created in 2008, are part of the Federal Education System and aim at training citizens to work actively in the world of work. The Subsequent Form, one of the ways in which the High School Technical Courses enable technical training and is intended for students who have already finished high school. The objective of this research was to compare the academic efficiency indexes of the subsequent courses, in the distance and on-site modalities, offered by the Federal Institute of Amapá (IFAP) in 2018. To this end, a bibliographical and documentary research was carried out, as to the approach, this study it is quanti-qualitative. The data were accessed on the Nilo Peçanha Platform (plataformanilopecanha.org). It was found that the Academic Efficiency of the Subsequent Technical Courses offered in the Face-to-face modality is greater than that of the Courses offered in the Distance modality. With regard to distance education, because it has lower Academic Efficiency when compared to classroom teaching, it is necessary that the institution develops actions to combat and prevent evasion. In conclusion, the need to foster other studies that investigate the problems related to dropout in Distance Education and that also propose other solutions to minimize dropout rates and raise the Academic Efficiency Index of Subsequent Courses offered in distance education by the Federal Institute of Amapá.